Hubungan Pengetahuan, Sikap Dan Paparan Media Sosial Youtube Terhadap Perilaku Merokok Pada Remaja SMAIT Bina Bangsa Sejahtera Kota Bogor Tahun 2024 - Syifa, Nadiatus; Aristi, Dela (Journal of Religion and Public Health, 2024)
Smoking  is  detrimental  to  health  and  is  commonly  practiced  by  adults  and  teenagers.  In  2019, WHO data shows that 19.2% of students aged 13-15 years used tobacco and more than 8 million deaths were caused by tobacco. This is due to a lack of knowledge aboutthe dangers of smoking and  exposure  to  negative  content  on  social  media  which  can  influence  teenagers'  attitudes towards  smoking.  This  study  aims  to  determine  the  relationship  between  knowledge,  attitudes and  exposure  to YouTube  social  media  on  smoking  behavior  among  teenagers  at  SMAIT  Bina Bangsa  Sejahtera  Bogor  City  with  a  cross-sectional  study  design  and  a  sample  of  156  people. This  research  is  quantitative  research  with  data  collection  through  questionnaires.  The  data analysis used in the research was univariate analysis and bivariate analysis using the Chi-square test.  The  research  results  showed  that  the  smoking  behavior  of  SMAIT  Bina  Bangsa  Sejahtera teenagers  was  30.8%  with  attitudes  supporting  smoking  at  51.3%,  and  teenagers  who  were exposed to negative and positive content on YouTube social media were 85.9%.  The results of the  analysis  showed  that  there  was  a  relationship  between  knowledge  and  attitudes  towards smoking  behavior.  Teenagers  are  expected  to  be  more  careful  in  receiving  information  from YouTube social media, choose trusted sources and limit the time they use YouTube each day.Keywords: Attitude, Smoking behavior, YouTube.